Da campo militare a capitale: Asmara colonia italiana e oltre - Casciato, Maristella (Incontri. Rivista europea di studi italiani, 2013)
The ‘Primitive colony’ of Eritrea, overlooking the shores of the Red Sea, or Mar Rosso,(from which comes ‘Eritrea’ or ‘Red Land’), saw successive stages of Italiancolonialism, with a robust increase during the years of Fascism. Asmara, a village that became the capital in 1891, still conserves an almost intact urban structure andarchitectural features from its half century of colonialism. The first expansion of Asmara was regulated by a scheme plan, approved in 1902, which included the area to the East of the original military outpost on the Mai Belà river. The grid pattern was marked by two major arteries, parallel to each other: the King’s Way (il Corso del Re) and the Queen’s Avenue (il Viale della Regina). After the space of a decade,Cavagnari’s plan was the first to separate the European settlement from the indigenouszone. The advent of Fascism did not have an immediate impact in Eritrea; by then thecapital had developed a well-integrated population. One is continuously surprised bytestimonies of the residents in Asmara in the Thirties, which express a state of mindshared by both colonizers and colonized, describing the city as: ‘beautiful [...] inhabited by a mixed race, Italians and Africans ... a lot of traffic, shops, cinemas andrestaurants...’ . It is commonplace to refer to ‘good Italian people’ (italiani bravagente), which is a most difficult viewpoint to abandon, and is also a most relevant perspective when considering the architectural patrimony of Asmara as a shared heritage. This paper aims to shed light on this mixture of narratives and to reread the modernity of Asmaran architecture as an added value to the contemporary history of the Eritrean nation.